Effect of drying methods on phenolic compounds, antioxidant activity and surface colour of the potentially valuable Moroccan seaweeds Gracilaria gracilis and Ulva lactuca: modelling the optimal treatment - Samira El Majnaoui; Mounia Lekrati; Said El Broudi; Fatiha Benkhalti; Naima Zehhar; Mimoun ElKaoua; Ahmed Belmouden; Abdellah Houari; Nadia El Kadmiri (Applied Phycology, 2025)
Gracilaria gracilis (Rhodophyta) and Ulva lactuca (Chlorophyta) are two common seaweeds in Morocco with important commercial potential. The impact of solar drying (SD), freeze-drying (FD) and oven convective drying (OD) on these seaweeds was assessed based on total polyphenol (TP) and total flavonoid (TF) contents, ortho-diphenol levels, antioxidant activity and colour stability. In U. lactuca, OD at 60°C resulted in the highest TP and TF retention, followed by OD at 40°C, which exhibited comparable effects to SD and FD in preserving flavonoids. For G. gracilis, OD at 60°C yielded TP and TF contents similar to those obtained via SD and FD, with the highest TP concentration observed after OD at 40°C, while TF retention was maximized with FD. Consequently, oven-drying at 60°C appears to be the most effective drying method for maintaining TP and TF levels in both species. The highest ortho-diphenol retention was recorded following FD and SD in both species, although OD at 25°C and 40°C also resulted in significant ortho-diphenol preservation. Similarly, FD, SD, and OD at 25°C resulted in the highest antioxidant activity, with a strong correlation between ortho-diphenol content and antioxidant capacity. Therefore, FD and SD effectively preserve antioxidant properties and ortho-diphenol content in both species, with OD at 25°C serving as a suitable alternative. Overall, OD presents a promising drying method for optimizing the conservation of bioactive compounds in seaweed, provided that drying parameters are carefully controlled (compared to SD), offering an economically viable solution (compared to FD). Indeed, all treatments retained a high level of brightness. FD also maintained the fresh colour of U. lactuca. Wang and Singh, and Page models were identified as the most suitable for optimizing OD kinetics of G. gracilis and U. lactuca, respectively.